Concurrent functional gastrointestinal disorders in patients with inflammatory bowel disease - Walker, Caroline; Boland, Anna; Carroll, Andrew; O’Connor, Anthony (Frontiers in Gastroenterology, 2022)
Approximately 25% of people with quiescent inflammatory bowel disease (IBD) have symptoms caused by a functional gastrointestinal disorder (FGID). The pathophysiology of FGIDs in IBD is multifactorial. The gut-brain axis plays an important role as a bidirectional pathway with reciprocal GI and psychological symptoms. Other factors include altered GI motility, microbiome dysbiosis, medication use, prior surgery, impaired intestinal permeability, immune-system activation, and visceral hypersensitivity. As both IBD and certain FGIDs can have similar symptoms, it can be difficult to determine which disorder is the precipitant of symptoms. However, the prompt diagnosis of an overlapping FGID helps avoid unnecessary corticosteroid use and escalations of IBD treatment. Despite their prevalence, there have been very few randomised control trials conducted on therapeutic interventions for overlapping FGIDs in IBD. Therefore, management usually follows that recommended for FGIDs, with certain adaptations made to allow for an altered GI anatomy and functioning caused by IBD.